Analisis Pengendalian dalam Fungsi Manajemen Perpustakaan pada Empat Jenis Perpustakaan di Indonesia - Arya Wijaya Pramodha Wardhana; Sofia Nur Aisyah; Laksmi Laksmi (Perpustakaan Nasional, 2023)
The presence of libraries is a familiar and common phenomenon in society, categorized into four types: public, special, school, and university libraries. However, in Indonesia, libraries face challenges, including financial resources, human resource issues, bureaucratic hurdles, physical resource problems, and information resource issues. These challenges have resulted in many libraries not meeting standards, despite guidelines set by the National Library of Indonesia. Libraries, integral to their management processes, often overlook a crucial function—control. This article delves into control as a key management function, addressing the problems encountered by Indonesian libraries. The focus is on control's role in overcoming issues, employing literature study methods and data analysis through observational literature techniques. The results indicate that all four types of libraries need to implement various techniques and analyses, including cost-benefit and return on investment analysis, benchmarking, leadership support, effective collaboration with librarians and technical staff, based on up-to-date information and corrective actions. Additionally, investments in infrastructure, facilities, information technology, digital resources, and information literacy training are essential.